Susceptibility of the Colorado Potato Beetle and the Sugarbeet Wireworm to Steinernema feltiae and S. glaseri - Toba, H. Harold (Society of Nematologists, 1983)
In laboratory tests, larvae of the Colorado potato beetle (CPB), Leptinotarsa decemlineata (Say), and the sugarbeet wireworm (SBW), Limonius californicus (Mannerheim), were exposed to the nematodes Steinernema feltiae Filipjev (Mexican strain) (= Neoaplectana carpocapsae) and S. glaseri Steiner in soil. S. feltiae caused significantly higher mortality in SBW larvae than did S. glaseri, but both nematode species were equally effective against CPB larvae. The minimum concentration of S. feltiae for 100% mortality of CPB larvae after 13 days was 157 nematodes/cm² of soil, and the LC₅₀ based on 6-day mortality was 47.5 nematodes/cm²; in contrast, 100% mortality of SBW larvae was not achieved with even the highest concentration tested, 393 nematodes/cm². CPB adults emerging from nematode-contaminated soil were not infected. In field cage tests, S. feltiae applied to the soil surface at the rates of 155 and 310 nematodes/cm² soil caused 59% and 71% mortality, respectively, of late-fourth-instar spring-generation CPB, and 28% and 29% mortality, respectively, of SBW. No infection was obtained when larvae of summer generation CPB and SBW were placed in the same cages approximately 6 weeks after nematodes were applied to the soil. Inundative soil applications of S. feltiae, though cost prohibitive at present, were effective in reducing caged CPB and SBW field populations.